2019
DOI: 10.1155/2019/1302015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immune Regulatory Cells in Nontraumatic Osteonecrosis of the Femoral Head: A Retrospective Clinical Study

Abstract: The immunologic factors have been implicated in the pathogenesis of osteonecrosis. We aimed to investigate the potential role of immune regulatory cells in the development of osteonecrosis of femoral head (ONFH). Sixty-seven patients diagnosed with ONFH and fifty-eight age-, height-, and weight-matched healthy subjects were included in this retrospective study between September 2015 and September 2018. The flow cytometry was used to test the count, percentage, and ratio of T and B lymphocyte subsets in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Recent studies have demonstrated that inflammatory processes are associated with the development and progression of osteonecrosis. Abnormal immune response, imbalanced immune cell subpopulations, and higher plasma levels of inflammatory cytokines in patients with osteonecrosis suggest that inflammation plays a crucial role in this disorder [ 12 14 ]. Moreover, chemokines and cytokines released by necrotic cells recruit inflammatory cells, inducing local and systemic immune response in patients with osteonecrosis [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that inflammatory processes are associated with the development and progression of osteonecrosis. Abnormal immune response, imbalanced immune cell subpopulations, and higher plasma levels of inflammatory cytokines in patients with osteonecrosis suggest that inflammation plays a crucial role in this disorder [ 12 14 ]. Moreover, chemokines and cytokines released by necrotic cells recruit inflammatory cells, inducing local and systemic immune response in patients with osteonecrosis [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, for the lack of typical symptoms and sensitive diagnostic indicators, it is sometimes difficult to predict and diagnose cases with SONFH and thus lose the optimal treatment opportunity. Moreover, as indicated from existing studies, immune cells primarily impact the development of SONFH (Ma et al, 2019). For this reason, there is profound significance in finding specific diagnostic markers and analyzing the pattern of infiltration of immune cells for improving the prognosis of SONFH cases.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence points to inflammatory osteoimmunology playing an indispensable role in the pathogenesis of ONFH. 4 - 8 …”
mentioning
confidence: 99%
“…While immune cells such as macrophages are important for resolving inflammation and promote subsequent tissue repair, they also contribute to ONFH, suggesting that the disease arises as a result of immune system dysfunction. 5 , 8 Bone biology and immunology have recently been combined in the field of osteoimmunology to become an important focus of ONFH research. 9 We will summarize the current understanding of the osteoimmunology of ONFH, focusing on the important roles of macrophages, T and B cells, and neutrophils, as well as related signalling molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation